Options Made Easy: Your Guide to Profitable Trading, Second Edition - Cohen, Guy (Financial Times Prentice Hall books., 2005)
In Options Made Easy , Second Edition, Guy Cohen clearly explains everything you need to know about options in plain English so that you can start trading fast and make consistent profits in any market, bull or bear! Simply and clearly, the author reveals secrets of options trading that were formerly limited to elite professionals-and exposes the dangerous myths that keep investors from profiting. As you set out on your options journey, you'll learn interactively through real-life examples, anecdotes, case studies, and pictures. Guy Cohen is your friendly expert guide, helping you pick the right stocks, learn the right strategies, create the trading plans that work, and master the psychology of the winning trader. Master all the essentials-and put them to work Options demystified so that you can get past the fear and start profiting! Learn the safest ways to trade options Identify high-probability trades that lead to consistent profits Design a winning Trading Plan-and stick to it Understand your risk profile and discover exactly when to enter and exit your trades Choose the right stocks for maximum profit Screen for your best opportunities-stocks that are moving-or are about to move Discover the optimum strategies for you Match your trading strategies to your personal investment goals No bull! The realities and myths of the markets What you must know about fundamental and technical analysis.